2012
DOI: 10.1186/1475-9276-11-55
|View full text |Cite
|
Sign up to set email alerts
|

A study of Iranian immigrants’ experiences of accessing Canadian health care services: a grounded theory

Abstract: BackgroundImmigration is not a new phenomenon but, rather, has deep roots in human history. Documents from every era detail individuals who left their homelands and struggled to reestablish their lives in other countries. The aim of this study was to explore and understand the experience of Iranian immigrants who accessed Canadian health care services. Research with immigrants is useful for learning about strategies that newcomers develop to access health care services.MethodsThe research question guiding this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…The studies were conducted in the US, [17][18][19][20][21][22][23] Canada, 24 England, [25][26][27] Scotland, 28,29 Ireland, 30 Netherlands, 31,32 Norway, 33 Sweden, 34 Finland, 35 Switzerland, 36 New Zealand, 37,38 and Australia. 39 Thirteen papers focused on refugees, three on asylum seekers, and seven combined both.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were conducted in the US, [17][18][19][20][21][22][23] Canada, 24 England, [25][26][27] Scotland, 28,29 Ireland, 30 Netherlands, 31,32 Norway, 33 Sweden, 34 Finland, 35 Switzerland, 36 New Zealand, 37,38 and Australia. 39 Thirteen papers focused on refugees, three on asylum seekers, and seven combined both.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies combined multiple ethnic groups, while four studies focused exclusively on people from Somalia, 17,19,21,38 and one each focused only on people from Bosnia, Ethiopia, Iran, Afghanistan, and Sri Lanka. 22,24,27,31,33 All selected studies used qualitative methods and collected data through interviews with individuals, families, or focus groups. Many used a grounded theory approach to analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Many studies have confirmed the presence of a "healthy immigrant effect": new immigrants arrive in a host country with a health advantage over their native-born counterparts, but experience a health decline over time. [3][4][5][6][7] This decline is evident when it comes to their self-reported general health status, chronic conditions, disabilities and mental health problems. 8 Crosssectional data showed that recent immigrants had better functional health and self-reported health, and lower disability, smoking and drinking rates compared to the Canadian-born population.…”
mentioning
confidence: 99%
“…One reason for immigration is claimed to be seeking better future (Dastjerdi, Olson, & Ogilvie, 2012). Then the mentioned transitions could be daunting, affecting social marginalization, loss of social networks (Lipsicas et al, 2012;Lipson & Meleis, 1983;Bhugra, 2005), health care access issues (Norredam, Mygind, & Krasnik, 2006), and adverse health consequences, including depression and anxiety (Grove & Zwi, 2006).…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 99%